Analysis of the Influence of Demography and Education on Youth Unemployment in Indonesia - Lanadimulya, Heri; Remi, Sutyastie Soemitro; Purnagunawan, Raden Muhamad (Universitas Pasundan, 2023)
This study analyses the influence of demography and education on youth unemployment in Indonesia. The demographic conditions are examined based on the youth population, adult unemployment, and sex ratio. Education is measured by the percentage of the labour force that has completed at least high school education. The model used is panel data regression analysis, employing time series data from 2013-2022 and cross-section data from 34 provinces in Indonesia. The study found that demographic conditions significantly influence youth unemployment levels in Indonesia. The increase in the number of young people needs to be managed so that their entry into the labour force is more manageable, by increasing the promotion of education and expanding skills training for young people. Adult unemployment is a competitor to the youth labour force, reducing the opportunity for young people to find employment, and the results of this study highlight that the distribution of women entering the labour force is smaller, so an increase in the number of men entering the labour force has a positive effect on the increase in youth unemployment. Meanwhile, increasing the proportion of the labour force with at least a high school education can reduce youth unemployment in Indonesia.